Actinomyces in Pregnancy: A Rare and Silent Cause of Preterm Delivery—Case Report - Philip E. Idaewor; Peter Ozua; Rotimi A. K. Jaiyesimi; Abdalla SAAD Abdalla Al-Zawi (Reproductive Medicine)
Background/Objective: Actinomyces is a genus of anaerobic gram-positive bacteria. It forms part of human body microbiota commonly in the oral cavity and genital tract. During pregnancy, the organism may cause the rare chorioamnionitis, where the maternal genital tract or other sites such as the oral cavity will be the likely source of the pathogen. This condition may increase the risk of foetal morbidity and mortality, and preterm birth. Methods: The placenta of a 33-year-female, primigravida, who presented with preterm labour and eventual delivery of baby at 20 weeks gestation was sent for histopathological examination. Her antenatal and clinical history were reviewed, to identify possible aetiology for her preterm birth. Results: She is noted to have presented with sudden per-vaginal creamy coloured discharge with no associated odour and no irritation. The discharge became blood staining associated with labour pain, this followed by premature spontaneous rupture of membrane and pre-mature labour. Laboratory tests revealed leucocytosis, neutrophilia, monocytosis, high CRP and elevated derived fibrinogen. The patient was delivered of a live male baby weighing 0.35 kg, who died shortly after birth. Placenta microscopic examination revealed patchy severe acute chorioamnionitis and prominent clusters of Gram-positive filamentous bacteria with histopathologic features of Actinomyces spp. The mother before discharged was treated with oral antibiotic. Conclusions: The intrauterine Actinomyces spp. infection is associated with preterm birth and neonatal mortality, early diagnosis during ante-natal could perhaps prevent preterm birth and reduce the associated neonatal mortality.